Uma interpretação do fenômeno jurídico-politico do município e sua inserção constitucional - Mourão, Carlos Figueiredo (2010)
The study aims to demonstrate the importance of Municipality in Brazilian democracy. It unravels the constitutional standard that inserted the municipality in the Brazilian Federation and the history of political and administrative institutions since Brazilcolony based on structuralism of the law. The study also points out that the dictates of the Constitution must be implemented. Therefore, it proposes an interpretation that favors local interest in the resolution of disputes of competence among the three spheres of the Federation